Comparative analysis of treatment strategies for groin injuries in athletes: Effects on successful recovery and recurrence of sports conditions – A systematic review - João Vitor de Castro Fernandes; Andre Pedrinelli; Jacobo Ángel Rubio-Arias (Apunts Sports Medicine)
Core muscle injuries, characterized by pubic region pain from muscle and tendon damage, present challenges in athletic recovery. Treatment for pubic pain in athletes often involves a combination of clinical approaches and surgical interventions, typically requiring long recovery periods. This study systematically reviews the treatment methods for groin pain in athletes and evaluates the return to sports outcomes. A total of 86 studies were reviewed, with 30 included in the qualitative analysis. The findings suggest a stepwise approach starting with conservative treatments, such as shockwave therapy, manual therapy, and exercise. If no improvement is observed within 3 to 6 months, surgery is considered. Procedures like adductor tenotomy and selective release have shown effectiveness in facilitating return to sports. Core muscle injuries require personalized treatment plans, with promising outcomes from conservative methods and effective surgical options for severe cases, leading to safe and complete recovery in most athletes. Level of evidence: 1